Studi Morfometrik Kepiting Rajungan (Portunus Pelagicus) - Umi Kalsum; Rivo Hasper Dimenta (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2023)
This study aims to reveal the morphometric characteristics crab P. pelagicus in the Sei Berombang estuary waters. The purposive sampling method used to determining 3 sampling stations, sampling process was using trawl nets. The results showed that the P. pelagicus population at Station 1 dominated by small carapace, at stations 2 and 3 found the domination of larger size with juvenile and adult phases category. The morphometric characters of carapace width (CW) in blue/flower crabs ranged from 9.50 to 17.40 cm, left posterolateral carapace length (LPCL) ranged from 2.20-6.70 cm, left anterolateral carapace length (LACL) ranged from 1.30-6.50 cm, right anterolateral carapace length (RACL) ranged from 1.20-7.00 cm, frontal right width (FRMW) ranged from 1.50-3.70 cm, carapace length (CH) ranged from 3.70-7.00 cm, internal carapace width (ICW) ranged from 6, 30-14.10 cm, right orbit (eye socket) width (ROW) ranged from 1.06-2.00 cm, left orbit (eye cavity) width (LOW) ranged from 1.12-2.10 cm, carapace width (CW) ranged from 9.50-17.40 cm, left posterolateral carapace length (LPCL) ranged from 2.20-6.70 cm, and left anterolateral carapace length (LACL) ranged from 1.30-6.50 cm. Conclusion, The morphometric characters of male and female P. pelagicus in the Sei Berombang waters were found to vary spatially and temporally. Kata Kunci: Characteristic Morphology, Identification, Morphometric, P. pelagicus